2020
DOI: 10.1177/0020764020940741
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic lockdown: An emotional health perspective of Indians on Twitter

Abstract: Background: Novel corona virus (2019-nCoV) has spread in the world since its first human infection in December 2019. India has also witnessed a rising number of infections since March 2020. The Indian government imposed lockdowns in the nation to control the movement of its citizens thereby confining the spread of the virus. Tweeters resorted to usage of social media platform to express their mind. Aim: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 6 publications
0
17
0
2
Order By: Relevance
“…However, in an online survey among mostly the residents of Hubei province, China average proportion of mental well-being was 49.4%, while in Germany 50% respondents reported anxiety and psychological distress [ 14 , 26 ]. In another online survey contemporary to the current study, mostly negative approach was reported during the later phase of lockdown [ 27 ]. Consistent with these observations, on overall calculation nearly 45% respondents were found to be at high risk of developing psychological distress, while more than half of the participants reported themselves as lonely and did not have high resilient coping ability.…”
Section: Discussionmentioning
confidence: 99%
“…However, in an online survey among mostly the residents of Hubei province, China average proportion of mental well-being was 49.4%, while in Germany 50% respondents reported anxiety and psychological distress [ 14 , 26 ]. In another online survey contemporary to the current study, mostly negative approach was reported during the later phase of lockdown [ 27 ]. Consistent with these observations, on overall calculation nearly 45% respondents were found to be at high risk of developing psychological distress, while more than half of the participants reported themselves as lonely and did not have high resilient coping ability.…”
Section: Discussionmentioning
confidence: 99%
“… Ref. Emotion Label Dataset Methodology adopted Lexicon/ Model used Advantages Limitations [32] Anger, Anxiety, Indignation, Negative emotion, Positive emotion Wiebo data pool Online Ecological Recognition (OER) LIWC2015 Lexicon For Policy improvement on mental health Case study on China from a social media platform [33] Anger, Anticipation, Disgust, Fear, Joy, Sadness, Surprise, Trust, positive, Negative Twitter dataset Lexicon-based approach NRC Word- Emotion Lexicon To understand the changing mindsets of people Only English tweets were collected for the study [35] Level of anxiety Online questionnaires ML-DL approach Hybrid Approach Understand psychological impact of epidemic on college students Online questionnaire [39] Anxiety, Fear, Sadness, Anger Questionnaire survey Lexical oriented approach. NRC Word-Emotion Association Lexicon To understand the coping strategies of nursing college students Online questionnaire [38] Willingness to self-isolate Online questionnaires Unsupervised learning Automated Model To help authorities understand public willingness to self-isolate Online questionnaire is used and study is restricted to U.S. only …”
Section: Related Workmentioning
confidence: 99%
“…The results also showed that the words of concern like "Health," "Family," and "Death" increased significantly, indicating that with passing the time, people were getting more concerned about their family and health. Another work [33] analyzed India's emotion during lockdown phase 2 and lockdown phase 3 on the Twitter dataset and analyzed the opinion on e-commerce during this pandemic. Their results showed a change in emotions during different lockdown phases.…”
Section: Related Workmentioning
confidence: 99%
“…Simultaneously, attention to group, religion, and emotions was more prevalent in Wuhan [ 18 ]. In India, a comparison between lockdown 2.0 (April 15 to May 3, 2020) and lockdown 3.0 (May 4 to May 17, 2020) revealed that the public's surprise, trust, fear, joy, and anger emotions decreased, but their anticipation, disgust, and sadness emotions increased [ 19 ]. However, policies such as physical distancing measures affected different emotions differently.…”
Section: Introductionmentioning
confidence: 99%